Policy Capacity and Community Empowerment as Instruments of Indonesia's Social Development in the era of Covid-19 Pandemic - Ahmad Sururi; Budi Hasanah (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
This research aims to discuss policy capacity within the scope of social, analytical and political capacity as an instrument of social development in the Covid-19 pandemic era. in Indonesia. These three aspects are important to study in depth because they have implications related to aspects of community empowerment. The research method used is a qualitative approach through a survey search of relevant academic literature from various sources, namely electronic media, journals, books, and government documents. The results show that social, analytical and political capacity can be operationalized through aspects of community empowerment which include processes, communities and organizations, active participation, and access to resources as instruments of social development in the Covid-19 pandemic era. All three are complementary and have very important implications, especially in supporting community empowerment policy efforts in the Covid-19 pandemic era through patterns and relationships that are able to provide strengthening to the community to be empowered and independent.